Neonatal management in premature babies: advances in Peru - Ota Nakasone, Arturo (2018)
Neonatology continues rapid progress in the last decades due to the increase in premature babies. Babies born before term have increased morbidity because of immaturity of most organs and systems. There is an inverse correlation between gestational age and morbidity. Management of extreme premature babies is a great challenge for neonatologists due to the high mortality. In this article we review the milestones in the management of premature babies, which began in the 70s, and include not only in equipment technologic advances, but also advance in knowledge on fetal and neonatal physiology and follow up programs of these patients. We also review the history of neonatology in Peru and advances in the treatment of premature babies resulting in lower neonatal mortality and improvement of the viability limits.